2005
DOI: 10.1016/j.jpainsymman.2004.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Correlates of Fatigue in HIV/AIDS

Abstract: Variation in the intensity of fatigue according to selected demographic, cultural, and health/illness variables was explored in 372 patients with HIV/AIDS, and the contribution of fatigue to physical and mental health in this population was investigated within the UCSF Symptom Management Model (UCSF-SMM). The sample included 73% African Americans and 63% males. Moderate to severe fatigue intensity was reported by 58% of the total sample. Women, Hispanics, the disabled and those with inadequate income or insura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
65
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 26 publications
10
65
2
Order By: Relevance
“…Studies of physiological correlates of fatigue report conflicting findings about relationships between fatigue and CD4? T-cell count [12,13] or viral load [6,7,11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of physiological correlates of fatigue report conflicting findings about relationships between fatigue and CD4? T-cell count [12,13] or viral load [6,7,11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue is the most frequent and debilitating complaint of HIV-positive people, with prevalence rates of up to 98% in studies of seropositive individuals (e.g., Anandan, Braveman, Kielhofner, & Forsyth, 2006;Breitbart, McDonald, Rosenfeld, Monkman, & Passik, 1998;Coleman et al, 2006;Duran et al, 2001;Fontaine, Larue, & Lassauniere, 1999;Henderson, Safa, Easterbrook, & Hotopf, 2005;Molassiotis, Callaghan, Twinn, & Lam, 2001;Norval, 2004;Simmonds, Novy, & Sandoval, 2005;Sullivan, Dworkin, & the Adult and Adolescent Spectrum of HIV Disease Investigators, 2003;Vogl et al, 1999;Voss, 2002Voss, , 2005. The consequences of fatigue include having to stop working, limiting one's involvement with family and friends, being unable to manage one's finances, and needing an entire day to get through the simplest of household chores (Anandan et al, 2006;Barroso, 2001;Jenkin, Koch, & Kralik, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to demographic and illness-related variables in studies of HIV-infected individuals, higher fatigue intensity has been reported in women, Hispanics, disabled subjects, those with a lower income, and those with no health insurance (Voss, 2005). Intravenous (IV) Phone (Harmon): 919.681.4846, FAX (Harmon): 919.681.8899, Email: harmo002@mc.duke.edu.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of the prevalence of fatigue in HIV-positive individuals when measured by self-report generally range from 55% to 65%, with similar estimates reported both before and since the advent of highly active antiretroviral therapy. [1][2][3][4][5] While some develop fatigue early in HIV infection, others develop fatigue with disease progression. 6 The consequences of fatigue include having to stop working, limiting one's involvement with family and friends, being unable to manage one's finances, and needing an entire day to get through the simplest of household chores.…”
mentioning
confidence: 99%